2005
DOI: 10.1002/bmc.556
|View full text |Cite
|
Sign up to set email alerts
|

A validated chiral HPLC method for the determination of mebeverine HCl enantiomers in pharmaceutical dosage forms and spiked rat plasma

Abstract: A new, precise, simple and accurate HPLC method was developed for the first time to separate and determine mebeverine enantiomers. Enantiomeric resolution was achieved on a cellulose Tris (3,5-dimethylphenyl carbamate) column known as Chiralcel OD, with UV detection at 263 nm. The mobile phase consisted of n-hexane, isopropyl alcohol and triethylamine (90:9.9:0.1 v/v/v). Sample run time was 18 min. On using the chromatographic conditions described, mebeverine enantiomers were well resolved with mean retention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…It has been used for the quantitative determination of mebeverine HCl [11][12][13][14] and its stability in tablets [15], for the determination of 5-aminosalicylic acid (5-ASA) [16][17][18][19][20] and the stability of 5-ASA and its metabolites in plasma [21,22], for sulphasalazine [23,24] and for aspirin [25][26][27][28][29].…”
Section: Optimization Of the Lc Proceduresmentioning
confidence: 99%
“…It has been used for the quantitative determination of mebeverine HCl [11][12][13][14] and its stability in tablets [15], for the determination of 5-aminosalicylic acid (5-ASA) [16][17][18][19][20] and the stability of 5-ASA and its metabolites in plasma [21,22], for sulphasalazine [23,24] and for aspirin [25][26][27][28][29].…”
Section: Optimization Of the Lc Proceduresmentioning
confidence: 99%
“…Previous investigations have shown that donepezil in biological fluids can be detected using high‐performance liquid chromatography (HPLC) equipped with a ultraviolet (UV),6–12 fluorescence (FL),13, 14 or mass spectrometric (MS)15–19 detector. The HPLC/UV method has been used to determine donepezil in human plasma,12, 13, 15, 19 but the method is insensitive (≥1.0 ng/mL) and requires a large volume of blood sample (≥1.0 mL) 6–12. Radwan et al 12.…”
mentioning
confidence: 99%
“…The HPLC/UV method has been used to determine donepezil in human plasma,12, 13, 15, 19 but the method is insensitive (≥1.0 ng/mL) and requires a large volume of blood sample (≥1.0 mL) 6–12. Radwan et al 12. have reported a stereoselective HPLC/UV assay for determining donepezil enantiomers.…”
mentioning
confidence: 99%
“…A survey of the literature revealed that alprazolam can be estimated by spectrophotometry [5] and liquid chromatographic methods [6][7][8][9][10][11], individually or in combination with other drugs, while mebeverine can be estimated by liquid chromatographic methods individually or concurrently with other drugs [12][13][14][15][16]. The reported methods are highly sophisticated, costly, and time-consuming, often requiring special sample preparation.…”
Section: Introductionmentioning
confidence: 99%